LEARNING GALLERY METHOD'S IMPACT ON ELEMENTARY STUDENTS' SCIENCE COMPREHENSION - Susanti, Diah (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
Science is one of the compulsory subjects at the elementary school level. Science learning is intended so that students can understand various things in nature and use them in everyday life. Unfortunately, students' understanding of science learning at SD Z is still lacking, with 80% getting grades below the KKM. For this reason, there is a need for innovation in learning, one of which is through the gallery learning strategy. This prompted the researcher to conduct a study entitled Effects of the Gallery Learning Method on the Level of Students' Understanding of Science Learning at SD Z. The purpose of this study was to determine whether or not there was an effect of implementing gallery learning at SD Negeri Z. The research method used was descriptive quantitative, with data collection techniques through observation, questionnaires, and interviews. Then, the research data will be analyzed in depth through the SPSS program. The results showed that the gallery learning method had a positive and significant effect on student understanding, as evidenced by an increase in the number of students who passed the KKM by 75%.